Positive outlook of marriage and family in the new millenium - Ano, Julie Larai (Abuja, Nigeria : B. Anny Publishers, 2000)
Portrays the positive aspects of marraige and family life and encourages people to treat marriage as a good thing instead of being scared.
Includes bibliographical references.
oif 26/02/15
Loan
Keywords: Marriage; Family life; Families